Prognostic analysis in children with focal cortical dysplasia II undergoing epilepsy surgery: Clinical and radiological factors - Zhang, Siqi; Luo, Yi; Zhao, Yilin; Zhu, Fengjun; Jiang, Xianping; Wang, Xiaoyu; Mo, Tong; Zeng, Hongwu (Frontiers in Neurology, 2023)
Objective: To investigate the value of clinical profiles and radiological findings in assessing post-surgical outcomes in children with focal cortical dysplasia (FCD) Ⅱ, while exploring prognostic predictors for this disease. Methods: We retrospectively reviewed fifty patients with postoperative pathologically confirmed FCD Ⅱ from January 2016 to June 2021. The clinical profiles and preoperative radiological findings were measured and analyzed. The patients were classified into four classes based on the Engel Class Outcome System at the last follow-up. For the analysis, patients were divided into two categories only (Engel Ⅰ vs Engel Ⅱ-Ⅳ) and named as ( seizure-free vs non-seizure-free). Qualitative and quantitative factors were subsequently compared by groups using comparative statistics. Receiver operating characteristic (ROC) curves were used to identify the predictors of prognosis in children with FCD Ⅱ. Results: Thirty-seven patients (74%) had Engel class Ⅰ outcomes. The minimum post-surgical follow-up was one year. Patients who attained seizure freedom were older at epilepsy onset and less likely to have no apparent lesions on the preoperative MRI ("MRI-negative"). The non-seizure-free group exhibited a higher gray matter signal intensity ratio (GR) on 3D T1-MPRAGE images (p = 0.006), with a lower GR on T2WI images (p = 0.003) and FLAIR images (p = 0.032). The ROC curve indicated that the model that combined the GR value of all MRI sequences (AUC, 0.87; 95% CI, 0.77–0.97; p < 0.001; 86% sensitivity, 85% specificity) was able to predict prognosis accurately. Conclusion: Lesser age at onset or MRI-negative finding of FCD lesions suggest a poor prognosis for children with FCD Ⅱ. And the model consisting of GR values from three MRI sequences facilitates the prognostic assessment of FCD Ⅱ patients with subtle MRI abnormalities to prevent worse outcomes.